Pengaruh Kepuasan Kerja terhadap Organizational Citizenship Behaviour melalui Komitmen Organisasi sebagai Variabel Intervening - Jelita Dian Iswari; Anna Partina (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2021)
This study is related to how the effect of job satisfaction on organizational citizenship behavior with organizational commitment as an intervening variable at PT Kereta Api Indonesia (Persero) Operation Area VI Yogyakarta. Respondents in this study were 50 employees of PT Kereta Api Indonesia (Persero) Operation Area VI Yogyakarta. Data collection using a questionnaire and the analysis technique used in this study is path analysis. The results showed that the job satisfaction variable had a positive and significant effect on organizational citizenship behavior, the job satisfaction variable had a positive but not significant effect on the organizational commitment variable, and the organizational commitment variable had a positive but not significant effect on the organizational citizenship behavior variable. This study also found that organizational commitment could not mediate the relationship between job satisfaction variables and organizational citizenship behavior variables.